Nickel oxide nano-based perovskite solar cell and preparation method thereof

By using NiOx nanoparticles as hole transport layer in perovskite solar cells and introducing self-assembled single molecule layer, the problem of poor conductivity of traditional nickel oxide layers is solved, and the battery efficiency and stability are improved.

CN119767936APending Publication Date: 2025-04-04HUANENG CLEAN ENERGY RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993103.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In existing perovskite solar cells, the nickel oxide hole transport layer is prepared by magnetron sputtering, which has poor conductivity, which limits the improvement of battery efficiency.

Method used

NiOx nanoparticles (x=1.5~3) are used as the hole transport layer, and a nanoparticle layer is formed on the transparent conductive glass substrate by spin coating, and a self-assembled single molecule layer is introduced between the hole transport layer and the perovskite absorbing layer.

Benefits of technology

It improves charge transfer performance, reduces charge loss, improves the overall efficiency of solar cells, and improves the stability and service life of the cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767936A_ABST
    Figure CN119767936A_ABST
Patent Text Reader

Abstract

The invention provides a nickel oxide nano-based perovskite solar cell and a preparation method, the nickel oxide nano-based perovskite solar cell comprises a NiOx nano-particle hole transport layer, x in NiOx nano-particles is equal to 1.5-3, compared with a nickel oxide layer prepared through traditional magnetron sputtering, the adopted nickel oxide nano-particles have better conductivity, and the conductivity of the nickel oxide nano-particles is improved. The overall charge transmission performance of the battery can be improved; the battery efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells, and in particular to a nickel oxide nano-based perovskite solar cell and a preparation method thereof. Background Art

[0002] The name perovskite comes from the calcium titanate (CaTiO3) mineral first discovered in Russian ore by Russian geologist Lev Perovski in 1839. This mineral is named for its unique chemical composition and crystal structure, and has gradually attracted people's attention in subsequent scientific research. Perovskite in a narrow sense refers to the calcium titanate mineral itself, while perovskite in a broad sense covers ABX3-type compounds with a perovskite structure type. Due to their unique physical and chemical properties, these compounds have shown great research value and application potential in multiple disciplines such as physics, chemistry and materials science.

[0003] The research on perovskite solar cells began in the early 21st century, especially in 2009 when scientists first used perovskite materials (such as CH3NH3PbI3, CH3NH3PbBr3) as sensitizers in dye-sensitized solar cells and achieved a photoelectric conversion efficiency of about 4%. This breakthrough has laid a solid foundation for the development of high-efficiency perovskite photovoltaic technology and has aroused great interest in this field among scientists around the world.

[0004] In the following decade, the research on perovskite solar cells has made rapid progress. By continuously optimizing the material composition, preparation process and device structure, the photoelectric conversion efficiency of small-area single-junction perovskite solar cells prepared in the laboratory has exceeded 26.7%, and this efficiency improvement rate far exceeds that of traditional crystalline silicon cells. Perovskite solar cells are gradually becoming a bright new star in the field of solar cells with their advantages such as high efficiency, low cost and easy preparation, and are expected to replace crystalline silicon cells in the future and become the mainstream technology of the new generation of solar cells.

[0005] Although perovskite solar cells have shown great advantages in efficiency and cost, the nickel oxide hole transport layer used in the industrialization of perovskite is prepared by magnetron sputtering and has poor conductivity, which limits the efficiency improvement of industrialized perovskite cells. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a nickel oxide nano-based perovskite solar cell and a preparation method. Compared with the nickel oxide layer prepared by traditional magnetron sputtering, the nickel oxide nanoparticles have better conductivity, can improve the overall charge transfer performance of the battery and thus improve the battery efficiency.

[0007] To achieve the above-mentioned object, the present invention provides the following technical solution: a nickel oxide nano-based perovskite solar cell, comprising a NiOx nanoparticle hole transport layer, wherein x in the NiOx nanoparticles is 1.5-3.

[0008] Furthermore, the thickness of the hole transport layer is 20nm~40nm.

[0009] Furthermore, a NiOx nanoparticle solution is spin-coated on a substrate to prepare a NiOx nanoparticle hole transport layer, wherein the concentration of the NiOx nanoparticle solution is 10 mg / ml to 20 mg / ml.

[0010] Furthermore, the NiOx nanoparticle solution is spin-coated on the substrate at a rotation speed of 3000 rpm to 4000 rpm for a spin-coating time of 25 s to 35 s to obtain a hole transport layer.

[0011] Furthermore, the substrate is made of transparent conductive glass, the transparent conductive glass is indium tin oxide, and the thickness of the substrate is 200nm~400nm.

[0012] Furthermore, a self-assembled monolayer, a perovskite light absorption layer, an electron transport layer and a top electrode are sequentially arranged on the NiOx nanoparticle hole transport layer, wherein: The thickness of the self-assembled monolayer is 1 nm to 5 nm, and the self-assembled monolayer is prepared by using at least one of MeO-2PACz, 2PACz, Me-4PACz and 4PACz; The thickness of the perovskite light absorption layer is 300nm~700nm, and the perovskite light absorption layer adopts (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 preparation; The thickness of the electron transport layer is 10nm~100nm, and the electron transport layer is TiO2, SnO2 or fullerene and fullerene derivatives; The thickness of the top electrode is 50nm~500nm, and the top electrode is made of gold, silver, copper, graphite or amorphous carbon.

[0013] The present invention also provides a method for preparing a nickel oxide nano-based perovskite solar cell, the specific steps of which are as follows: A NiOx nanoparticle solution with a concentration of 10 mg / ml to 20 mg / ml is spin-coated on a transparent conductive glass substrate to obtain a hole transport layer; Spin-coat a self-assembled monolayer solution with a concentration of 0.3 mg / ml to 1.2 mg / ml on the hole transport layer to obtain a self-assembled monolayer; Preparation on self-assembled monolayer (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite light absorbing layer; An electron transport layer and a top electrode are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell.

[0014] Furthermore, in the step of spin coating a NiOx nanoparticle solution with a concentration of 10 mg / ml to 20 mg / ml on a transparent conductive glass substrate to obtain a hole transport layer, the spin coating conditions are: a rotation speed of 3000 rpm to 4000 rpm and a spin coating time of 25 s to 35 s.

[0015] Further, a self-assembled monolayer solution with a concentration of 0.3 mg / ml to 1.2 mg / ml is spin-coated on the hole transport layer to obtain a self-assembled monolayer: the spin-coating conditions are: a rotation speed of 2000 rpm to 4000 rpm, a spin-coating time of 30 s to 40 s, and a self-assembled monolayer is obtained.

[0016] Furthermore, the self-assembled monolayer was prepared (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The step of perovskite light absorbing layer: prepare (FA) with a concentration of 1.5 mol / L according to the stoichiometric ratio 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, apply the perovskite precursor solution on the self-assembled monolayer, spin coating at a speed of 2000 rpm for 10 seconds, spin coating at a speed of 5000 for 40 seconds, quickly add 200 microliters of chlorobenzene 15 seconds before the end of spin coating, anneal at 100°C for 30 minutes to form a perovskite light-absorbing layer.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The nickel oxide nano-based perovskite solar cell provided by the present invention adopts NiOx nanoparticles (x=1.5~3) as a hole transport layer. Compared with the nickel oxide layer prepared by traditional magnetron sputtering, the NiOx nanoparticles have a larger specific surface area and more active sites, which is beneficial to the transmission and separation of charges, thereby reducing the loss of charges during the transmission process and improving the overall efficiency of the battery.

[0018] Furthermore, the present invention introduces a self-assembled monolayer between the hole transport layer and the perovskite light absorption layer. This self-assembled monolayer not only plays an isolation role, preventing direct contact and possible adverse reactions between nickel oxide and perovskite, but also optimizes the interface energy level matching, further promoting the transfer of charges. At the same time, the introduction of the self-assembled monolayer also improves the stability of the battery and extends the service life of the battery.

[0019] Furthermore, the perovskite light absorbing layer adopts (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3, this material has excellent light absorption properties and charge separation capabilities. Through the synergistic effect with the NiOx nanoparticle hole transport layer and the self-assembled monolayer, the perovskite light absorption layer can more efficiently capture sunlight and convert it into electrical energy.

[0020] The preparation method of the present invention sequentially coats a NiOx nanoparticle solution and a self-assembled monolayer solution on a transparent conductive glass substrate by spin coating to form a uniform and dense hole transport layer and a self-assembled monolayer. This preparation method not only avoids a complex high-temperature sintering process, but also reduces production costs.

[0021] Furthermore, the perovskite light-absorbing layer was prepared by a two-step spin coating method. By precisely controlling the spin coating speed and the time for adding the anti-solvent, a high-quality perovskite film was successfully prepared. This preparation method not only improves the crystal quality and optoelectronic properties of the perovskite light-absorbing layer, but also achieves precise control of the thickness of the perovskite film.

[0022] Furthermore, the electron transport layer and the top electrode are deposited by vacuum evaporation or other suitable deposition techniques to ensure close contact between the layers and good charge transfer performance. The entire preparation process is not only simple and efficient, but also the prepared perovskite solar cells have excellent performance and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic structural diagram of a perovskite solar cell prepared by the present invention; In the attached figure: 1, substrate; 2, hole transport layer; 3, self-assembled monolayer; 4, perovskite light absorption layer; 5, electron transport layer; 6, top electrode. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0025] like Figure 1As shown, the present invention provides a nickel oxide nano-based perovskite solar cell, which includes, from top to bottom, a substrate 1, a hole transport layer 2, a self-assembled monolayer 3, a perovskite light absorption layer 4, an electron transport layer 5 and a top electrode 6. In the present invention, the substrate 1 adopts transparent conductive glass, and the transparent conductive glass is indium tin oxide (FTO). The thickness of the substrate is 200nm~400nm, preferably 250nm~350nm; specifically 290nm, 300nm, 310nm, 320nm, etc.; the thickness of the nickel oxide nanoparticles in the hole transport layer is 20nm~40nm; the self-assembled monolayer The thickness of the layer is 1nm~5nm, preferably 1nm~3nm, and more preferably 1nm~2nm; the thickness of the perovskite light absorbing layer is 300nm~700nm, preferably 300nm~500nm, and more preferably 400nm~500nm; the thickness of the electron transport layer is 10nm~100nm, preferably 20nm~80nm, more preferably 30nm~60nm, and most preferably 40nm~50nm; the thickness of the top electrode is 50nm~500nm, preferably 100nm~400nm, and more preferably 100nm~200nm.

[0026] The preparation method of the above perovskite solar cell is specifically as follows: (1) Spin coating a NiOx nanoparticle solution on a transparent conductive glass substrate at a rotation speed of 3000 rpm to 4000 rpm for a spin coating time of 25 s to 35 s to obtain a hole transport layer; Preferably, in the NiOx nanoparticles, x=1.5-3, and the concentration of the NiOx nanoparticle solution is 10 mg / ml-20 mg / ml; (2) Spin coating the self-assembled monolayer solution on the hole transport layer at a rotation speed of 2000 rpm to 4000 rpm for 30 s to 40 s to obtain a self-assembled monolayer. The preparation of the self-assembled monolayer can prevent the reaction between nickel oxide and perovskite. Preferably, the concentration of the self-assembled monolayer solution is 0.3 mg / ml to 1.2 mg / ml.

[0027] Preferably, the self-assembled monolayer is prepared by using one or more of (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid MeO-2PACz, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid 2PACz, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid Me-4PACz or [4-(9H-carbazole-9-yl)butyl]phosphonic acid 4PACz, more preferably MeO-2PACz; (3) Preparation of perovskite light-absorbing layer on the self-assembled monolayer; Preferably, the perovskite light absorbing layer adopts (FA 0.95 MA0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 preparation; (4) depositing an electron transport layer on the perovskite light absorbing layer, wherein the electron transport layer is TiO2, SnO2 or one of fullerene and fullerene derivatives, more preferably C60; (5) A top electrode is deposited on the electron transport layer. The top electrode is made of one of gold, silver, copper, graphite or amorphous carbon, and is more preferably made of gold.

[0028] Embodiment 1: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0029] A 15 mg / mL NiOx nanoparticle solution (solvent: water) was spin-coated on a FTO glass substrate at 3000 rpm for 30 s and annealed for 10 minutes to form a hole transport layer NiOx.

[0030] A 0.6 mg / mL MeO-2PACz solution (solvent: isopropanol) was spin-coated on the hole transport layer at 3000 rpm for 30 seconds and annealed for 10 minutes to form a self-assembled monolayer.

[0031] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100 μL of the precursor solution and apply it on the self-assembled monolayer, spin coating at 2000 rpm for 10 s, spin coating at 5000 rpm for 40 s, quickly add 200 μL of chlorobenzene as anti-solvent 15 s before the end of spin coating, and then anneal the perovskite film at 100 °C on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400 nm.

[0032] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 , thickness is about 40nm.

[0033] Finally, a gold top electrode with a thickness of about 100 nm is prepared by vacuum evaporation to obtain a solar cell.

[0034] Embodiment 2: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0035] A 20 mg / mL NiOx nanoparticle solution (solvent: water) was spin-coated on a FTO glass substrate at 4000 rpm for 25 s and annealed for 10 minutes to form a hole transport layer NiOx.

[0036] A 0.6 mg / mL 2PACz solution (solvent: isopropanol) was spin-coated on the hole transport layer at 2000 rpm for 35 seconds and annealed for 10 minutes to form a self-assembled monolayer.

[0037] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100 μL of the precursor solution and apply it on the self-assembled monolayer, spin coating at 2000 rpm for 10 s, spin coating at 5000 rpm for 40 s, quickly add 200 μL of chlorobenzene as anti-solvent 15 s before the end of spin coating, and then anneal the perovskite film at 100 °C on a hot stage for 30 minutes to form a perovskite light-absorbing layer.

[0038] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 .

[0039] Finally, a silver material top electrode is prepared by vacuum evaporation to obtain a solar cell.

[0040] Embodiment 3: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0041] A 10 mg / mL NiOx nanoparticle solution (solvent: water) was spin-coated on a FTO glass substrate at 3500 rpm for 35 s and annealed for 10 min to form a hole transport layer NiOx.

[0042] A 0.6 mg / mL Me-4PACz solution (solvent: isopropanol) was spin-coated on the hole transport layer at 4000 rpm for 40 seconds and annealed for 10 minutes to form a self-assembled monolayer.

[0043] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100 μL of the precursor solution and apply it on the self-assembled monolayer, spin coating at 2000 rpm for 10 s, spin coating at 5000 rpm for 40 s, quickly add 200 μL of chlorobenzene as anti-solvent 15 s before the end of spin coating, and then anneal the perovskite film at 100 °C on a hot stage for 30 minutes to form a perovskite light-absorbing layer.

[0044] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 .

[0045] Finally, a copper material top electrode is prepared by vacuum evaporation to obtain a solar cell.

[0046] Embodiment 4: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0047] A 15 mg / mL NiOx nanoparticle solution (solvent: water) was spin-coated on a FTO glass substrate at 3000 rpm for 30 s and annealed for 10 minutes to form a hole transport layer NiOx.

[0048] A 0.3 mg / mL 4PACz solution (solvent: isopropanol) was spin-coated on the hole transport layer at 3000 rpm for 30 seconds and annealed for 10 minutes to form a self-assembled monolayer.

[0049] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100 μL of the precursor solution and apply it on the self-assembled monolayer, spin coating at 2000 rpm for 10 s, spin coating at 5000 rpm for 40 s, quickly add 200 μL of chlorobenzene as anti-solvent 15 s before the end of spin coating, and then anneal the perovskite film at 100 °C on a hot stage for 30 minutes to form a perovskite light-absorbing layer.

[0050] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 .

[0051] Finally, a top electrode of graphite material is prepared by vacuum evaporation to obtain a solar cell.

[0052] Embodiment 5: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0053] A 15 mg / mL NiOx nanoparticle solution (solvent: water) was spin-coated on a FTO glass substrate at 3000 rpm for 30 s and annealed for 10 minutes to form a hole transport layer NiOx.

[0054] 1.2 mg / mL MeO-2PACz and 4PACz solution (solvent: isopropanol) was spin-coated on the hole transport layer at 3000 rpm for 30 s and annealed for 10 minutes to form a self-assembled monolayer.

[0055] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution (concentration is 1.5 mol / L, solvent is DMF:DMSO=4:1), take 100 μL of the precursor solution and apply it on the self-assembled monolayer, spin coating at 2000 rpm for 10 s, spin coating at 5000 rpm for 40 s, quickly add 200 μL of chlorobenzene as anti-solvent 15 s before the end of spin coating, and then anneal the perovskite film at 100 °C on a hot stage for 30 minutes to form a perovskite light-absorbing layer.

[0056] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 .

[0057] Finally, the amorphous carbon material top electrode is prepared by vacuum evaporation to obtain a solar cell.

[0058] Comparative Example: The FTO glass substrate was cleaned with acetone, isopropanol and deionized water in turn, and then dried for later use.

[0059] A hole transport layer NiOx with a thickness of about 20 nm was formed on the FTO glass substrate by magnetron sputtering.

[0060] An aluminum oxide nanoparticle solution (nanoparticle size 30 nm, concentration 1 mg / mL, solvent is isopropanol) was spin-coated on the hole transport layer at 5000 rpm for 30 s and annealed for 10 minutes to form an Al2O3 dielectric layer.

[0061] Formulated according to stoichiometric ratio (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05)3 Perovskite precursor solution (concentration is 1.5mol / L, solvent is DMF:DMSO=4:1), take 100 microliters of precursor solution and apply it on the dielectric layer, spin coating at 2000rpm for 10s, spin coating at 5000rpm for 40s, quickly add 200 microliters of chlorobenzene as anti-solvent 15s before the end of spin coating, and then anneal the perovskite film at 100℃ on a hot stage for 30 minutes to form a perovskite light-absorbing layer with a thickness of about 400nm.

[0062] The electron transport layer C is prepared on the passivation layer by vacuum evaporation on the perovskite layer. 60 , thickness is about 40nm.

[0063] Finally, the metal electrode gold is prepared by vacuum evaporation method with a thickness of about 100nm to obtain a solar cell.

[0064] The performance of the solar cells prepared in Example 1 and Comparative Example 1 was tested. Under room temperature, a 3A solar simulator was used to test the performance of the solar cells at 100 mW / cm 2 The conversion efficiency of the cells prepared in Example 1 and Comparative Example 1 was tested under a light intensity of 0.084 cm 2 .

[0065] The test results of the battery prepared in the embodiment are as follows:

[0066] The performance test results of the bottom battery prepared in the comparative example are as follows:

[0067] From the battery test results in the table, it can be seen that the battery performance prepared in Example 1 is significantly improved compared with the control example, which indicates that the use of nickel oxide nanoparticles has better conductivity than the nickel oxide layer obtained by magnetron sputtering, and the filling factor and open circuit voltage are significantly improved.

Claims

1. A nickel oxide nano-based perovskite solar cell, characterized in that: It includes a NiOx nanoparticle hole transport layer, wherein x in the NiOx nanoparticles is 1.5-3.

2. A nickel oxide nano-based perovskite solar cell according to claim 1, characterized in that: The thickness of the hole transport layer is 20nm-40nm.

3. The nickel oxide nano-based perovskite solar cell according to claim 1, characterized in that: The NiOx nanoparticle solution is spin-coated on a substrate to prepare a NiOx nanoparticle hole transport layer, wherein the concentration of the NiOx nanoparticle solution is 10 mg / ml-20 mg / ml.

4. A nickel oxide nano-based perovskite solar cell according to claim 3, characterized in that: The NiOx nanoparticle solution was spin-coated on the substrate at a rotation speed of 3000 rpm to 4000 rpm for a spin-coating time of 25 s to 35 s to obtain a hole transport layer.

5. The nickel oxide nano-based perovskite solar cell according to claim 3, characterized in that: The substrate is made of transparent conductive glass, the transparent conductive glass is indium tin oxide, and the thickness of the substrate is 200nm-400nm.

6. The nickel oxide nano-based perovskite solar cell according to claim 1, characterized in that: The NiOx nanoparticle hole transport layer is provided with a self-assembled monolayer, a perovskite light absorption layer, an electron transport layer and a top electrode in sequence, wherein: The thickness of the self-assembled monolayer is 1 nm to 5 nm, and the self-assembled monolayer is prepared by using at least one of MeO-2PACz, 2PACz, Me-4PACz and 4PACz; The thickness of the perovskite light absorption layer is 300nm~700nm, and the perovskite light absorption layer adopts (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 preparation; The thickness of the electron transport layer is 10nm~100nm, and the electron transport layer is TiO2, SnO2 or fullerene and fullerene derivatives; The thickness of the top electrode is 50nm~500nm, and the top electrode is made of gold, silver, copper, graphite or amorphous carbon.

7. The method for preparing a nickel oxide nano-based perovskite solar cell according to claim 6, characterized in that: The specific steps are as follows: A NiOx nanoparticle solution with a concentration of 10 mg / ml to 20 mg / ml is spin-coated on a transparent conductive glass substrate to obtain a hole transport layer; Spin-coat a self-assembled monolayer solution with a concentration of 0.3 mg / ml to 1.2 mg / ml on the hole transport layer to obtain a self-assembled monolayer; Preparation on self-assembled monolayer (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite light absorbing layer; An electron transport layer and a top electrode are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell.

8. The method for preparing a nickel oxide nano-based perovskite solar cell according to claim 7, characterized in that: In the step of spin coating a NiOx nanoparticle solution with a concentration of 10 mg / ml to 20 mg / ml on a transparent conductive glass substrate to obtain a hole transport layer, the spin coating conditions are: a rotation speed of 3000 rpm to 4000 rpm and a spin coating time of 25 s to 35 s.

9. The method for preparing a nickel oxide nano-based perovskite solar cell according to claim 7, characterized in that: The self-assembled monolayer solution with a concentration of 0.3 mg / ml to 1.2 mg / ml is spin-coated on the hole transport layer to obtain the self-assembled monolayer. The spin-coating conditions are: a rotation speed of 2000 rpm to 4000 rpm, a spin-coating time of 30 s to 40 s, and a self-assembled monolayer is obtained.

10. The method for preparing a nickel oxide nano-based perovskite solar cell according to claim 7, characterized in that: Preparation on self-assembled monolayer (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The step of perovskite light absorbing layer: prepare (FA) with a concentration of 1.5 mol / L according to the stoichiometric ratio 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, apply the perovskite precursor solution on the self-assembled monolayer, spin coating at a speed of 2000 rpm for 10 seconds, spin coating at a speed of 5000 for 40 seconds, quickly add 200 microliters of chlorobenzene 15 seconds before the end of spin coating, anneal at 100°C for 30 minutes to form a perovskite light-absorbing layer.